Cultural Heritage Development Model of Sukuh Temple as A Sustainable Cultural Tourism - Mulyantari , Enny; Rosilawati, Yeni (Technium Social Sciences Journal, 2021)
The current model of cultural tourism development in Indonesia is sustainable cultural tourism. This tourism model is not solely aimed at earning income but also concerns the impact on both the community and tourist attractions. This research was conducted in the tourist destination of Sukuh Temple, Karanganyar Regency, one of the cultural heritages in Central Java. This study aims to improve the organization of tourism promotion and explain the development strategy of Sukuh Temple Site as a cultural tourism attraction. This research is a qualitative study that sees research as a process to gain a deep understanding of the interaction of a community. A SWOT analysis technique analyzed the internal factors of strengths and weaknesses and external factors of opportunities and threats. The study results uncovered that Sukuh Temple is a distinctive, attractive, and informative cultural tourism attraction with a high selling point.